Imagined Selves: Mediating Desires and Subject Positions in the Japanese Literati Art of Okuhara Seiko (1837–1913) - Wakamatsu, Yurika (Archives of Asian art, 2020)
Beauty by Plum and Window, a hanging scroll produced in 1907 by the Japanese artist Okuhara Seiko, calls into question fundamental presumptions about literati art, a mode of art-making often seen as a means of self-representation. Instead of creating a singular subject that indexes the artist's self, this work deploys diverse pictorial and literary tropes to construct multiple personae, enabling the viewer (including the artist) to shift among them. The scroll effects the viewer's movement from one subject position to another, undermining the binary of spectator and spectacle, heterosexual relationship and homosocial bond, and subject and object. Engaging with Bruno Latour's actor-network theory, this article argues that if we do not assume a direct alignment between the subject of representation and the represented subject, a literati artwork can become a mediator of multiple shifting “selves” rather than an extension of a singular, unified “I.” Literati art thus functions not merely as a repository of self-expression but also as a generative mediator of identities and social relations. In staging multivalent modes of engagement, Seiko's scroll ultimately offers an alternative perspective on the role of subjectivity in the interpretation of literati art.